Evaluación de los Microorganismos eficaces (E.M) en producción de abono orgánico a partir del estiércol de aves de jaula (2001)
ABSTRACT: An evaluation of the transformation process of caged hens’ dung into organic fertilizer, was carried out in this study in order to recognize the performance of efficient microorganisms (EM) upon the physical and chemical composition of the compost. The used methodology considers an aerobic process by means of mechanical removal of the material, weekly samples were taken for humidity and pH measurements, at the end of the process analysis to determine the products quality were done. The work was done under a random unrestricted design (RUD) with a control group and two treatments, five replicas for each one. According to the results the process of compost formation was produced between the second and fourth week and the drying from the fifth to the sixth week for al¡ the treatments. The mixture of the manure and the EM however, showed a statistically significant difference (p<0.05) in pH with regard to the other treatments, showing a faster descent (below 8.5), which indicates the positive effect in the acceleration of the compost stabilization process with the addition of EM. The physical and chemical tests carried out at the end show greater values of nitrogen and potassium for the mixture of hens’ dung and EM.